2015
DOI: 10.1007/s00213-015-4006-y
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant approach-avoidance conflict resolution following repeated cocaine pre-exposure

Abstract: Repeated cocaine pre-exposure allows appetitive approach motivations to gain greater influence over behavioral output in the context of motivational conflict, due to aberrant positive and negative incentive motivational processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…Thus, the association between longer duration of stimulant use and greater reductions in responses in frontal regions suggests stimulant use could also impact on the regulatory control of emotion circuits. This fits with preclinical work showing that repeated stimulant exposure reduces learning to aversive cues (Nguyen et al 2015).…”
supporting
confidence: 87%
“…Thus, the association between longer duration of stimulant use and greater reductions in responses in frontal regions suggests stimulant use could also impact on the regulatory control of emotion circuits. This fits with preclinical work showing that repeated stimulant exposure reduces learning to aversive cues (Nguyen et al 2015).…”
supporting
confidence: 87%
“…While it may be tempting to attribute the present effect of ventral HPC lesions upon the conflict test simply to a reduction in anxiety, it is important to note that our measure of learned approach avoidance conflict does not invariably correlate with measures of unlearned anxiety such as the elevated plus maze. For instance, we have found that rats that had undergone repeated administration of cocaine exhibit marked preference for the mixed valence conflict cue compared to the neutral cue, in the absence of any changes in anxiety levels, as measured in the elevated plus maze (Nguyen et al, ). Furthermore, we would argue, that an aberrant state of anxiety is a product of deficient approach‐avoidance conflict resolution, and not the underlying source of aberrant approach‐avoidance conflict resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to these studies, others have reported that a similar CIE exposure protocol resulted in insensitivity to punished alcohol seeking in an operant self‐administration paradigm (Radke et al., ). In addition, a history of exposure to cocaine promotes reward seeking under conflict in males (Nguyen et al., ). Thus, we had anticipated that CIE would promote compulsivity in males.…”
Section: Discussionmentioning
confidence: 99%